2020
DOI: 10.1016/j.cortex.2020.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Changes in visual cortical processing attenuate singleton distraction during visual search

Abstract: The ability to suppress distractions is essential to successful completion of goal-directed behaviors. Several behavioral studies have recently provided strong evidence that learned suppression may be particularly efficient in reducing distractor interference. Expectations about a distractor's repeated location, color, or even presence is rapidly learned and used to attenuate interference. In this study, we use a visual search paradigm in which a color singleton, which is known to capture attention, occurs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
69
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(87 citation statements)
references
References 98 publications
(138 reference statements)
14
69
4
Order By: Relevance
“…For "non-target 1" (the item neighboring the target on the side opposite the distractor), there was an overall history related modulation (color constant > color variable, p = .016, η 2 p = .42) that did not interact with ROI (p = .76, η 2 p = .03). Similar general effects on non-target processing have been observed recently 51 and may reflect a bias of attention away from the distractor such that attention may 'overshoot' the target because of the reduction in signal at the distractor location. The effect of history on "non-target 1" responses likewise was similar though of borderline significance in the GLM analysis (color constant > color variable, p = .049, η p = .31).…”
Section: Behaviorsupporting
confidence: 75%
See 1 more Smart Citation
“…For "non-target 1" (the item neighboring the target on the side opposite the distractor), there was an overall history related modulation (color constant > color variable, p = .016, η 2 p = .42) that did not interact with ROI (p = .76, η 2 p = .03). Similar general effects on non-target processing have been observed recently 51 and may reflect a bias of attention away from the distractor such that attention may 'overshoot' the target because of the reduction in signal at the distractor location. The effect of history on "non-target 1" responses likewise was similar though of borderline significance in the GLM analysis (color constant > color variable, p = .049, η p = .31).…”
Section: Behaviorsupporting
confidence: 75%
“…Of course, these possibilities are not mutually exclusive. For example, distractor and target processing seem to be differentially affected by history [49][50][51][52] . Therefore, it may be that history-driven changes to priority are reflected in a combination of traditionally 'goal-driven' and 'stimulus-driven' neural signatures of priority.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with a number of studies in the literature showing that distractor suppression improves with exposure (Awh, Matsukura, & Serences, 2003;Noonan et al, 2016;Turatto, Bonetti, Pascucci, & Chelazzi, 2018;Vatterott et al, 2018) and learning occurs rapidly (Vatterott et al, 2018;Vatterott & Vecera, 2012). While the specific mechanisms are still debated, it appears that learned suppression for distractor features operates in visual cortex, directly attenuating the attend-to-me signal and preventing attentional capture (Adam & Serences, 2020;van Moorselaar, Lampers, Cordesius, & Slagter, 2020;Won et al, 2020). Such results suggest that learned suppression attenuates the readout of visual information about the distractor.…”
Section: Discussionsupporting
confidence: 89%
“…These results lead to the prediction that the opposite should also be true: memory precision and awareness should decline as suppression improves. Such a result would be consistent with recent findings that reductions in distractor interference are related to mechanisms within visual cortex that prevent the "readout" of attentional priority signals to later stages of processing (Adam & Serences, 2020;Birman & Gardner, 2019;Won, Forloines, Zhou, & Geng, 2020).…”
Section: Introductionsupporting
confidence: 90%
“…The traces left in place during distractor filtering under these conditions are much more complex than those relative to their inhibition, and comprise a wealth of other types of processing, including a preliminary attentional selection based on their perceptual features 31 . Interestingly, recent studies have shown that in similar visual search tasks, if the perceptual features defining distractors are consistently used across trials (i.e., distractors appear more frequently in the same color or at the same location), the facilitation associated with their filtering is crucially linked with adaptations in the cortical activity of brain areas involved in visual processing as early as V1 59 , 60 . The reduced interference determined by these distractors might thus be justified by their impoverished low-level perceptual processing, which may be triggered by the detection of intertrial regularities in stimulus properties 60 .…”
Section: Discussionmentioning
confidence: 99%